Optimal selection of PMU locations for enhanced state estimation in smart grid - Rihan, M; Aness, M.A; Anees, M.D; Ahmad, M; Beg, M.S (Proceedings of third International Conference on Computational Intelligence and Information Technology, 2013)
Installation of modern sensing devices is an integral requirement in the transition of a conventional power grid to smart grid. Phasor measurements synchronized through GPS presents one such alternative to enhance the monitoring and control feature in the power grid. Due to the high financial implications, these units should be deployed optimally in the grid. The methods reported in the literature for optimal placement usually provide multiple solutions. This paper presents a criterion for selection of the best solution out of multiple combinations. The criterion is based on improving the state estimation results by the installation of phasor measurement units. The reason behind selection of this criterion is that all the downstream applications of contingency analysis; steady-state, voltage, and dynamic as well as the optimal power flow are dependent on the accuracy of the state estimation results. Because of its key role in energy management system, state estimation is set to be a vital function in the development of smart grid.